2000
DOI: 10.1002/(sici)1438-9312(200005)102:5<351::aid-ejlt351>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 1-monoacyIgIyceroIs from gIycidoI and fatty acids cataIyzed by the chromium(III)-fatty acid system

Abstract: A description is given for preparing 1‐monoacylglycerols by the reaction of fatty acids with glycidol catalyzed by Cr(III)‐fatty acid complexes. These complexes were found to possess catalytic efficiency substantially greater than catalysts employed earlier. Effects of catalyst type, its content in the mixture, molar ratio of reactants, and reaction temperature during the course of acid conversion were studied. With a catalyst content of 0.5% by mass of charged reactants and at 90 °C a 90— 95% conversion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
16
1
Order By: Relevance
“…Yakubov et al (1985) reported the same values for an analogous complex made from pentadecanoic acid. Although the UV/VIS spectrum of our DHA-chromium(III) complex shows the shift towards lower wavelengths, in agreement with the proposed structure of the oxo-centred trinuclear core, it is not in agreement with the structure inferred by Janis et al (2000).…”
Section: Discussioncontrasting
confidence: 79%
“…Yakubov et al (1985) reported the same values for an analogous complex made from pentadecanoic acid. Although the UV/VIS spectrum of our DHA-chromium(III) complex shows the shift towards lower wavelengths, in agreement with the proposed structure of the oxo-centred trinuclear core, it is not in agreement with the structure inferred by Janis et al (2000).…”
Section: Discussioncontrasting
confidence: 79%
“…The bacteria were subsequently grown at a temperature of 30 ± 1 °C for 24 h. Solutions and chemicals Monoglycerides were produced by adding an appropriate fatty acid to glycidol under the catalytic influence of chromic ions according to the method of Janiš et al (2000). The chemicals used were obtained from SigmaAldrich (St. Louis, USA).…”
Section: Methodsmentioning
confidence: 99%
“…MAGs with C-06:0 and C-08:0 were prepared as per Janis et al (2000) published earlier but by a modified procedure using copper acetate as the catalyst. Initially, the catalysts were prepared by the reaction of Cu(AcO) 2 .H 2 O with hexanoic acid and octanoic acid for the synthesis of 1-mono caproin and 1-mono caprylin respectively with toluene as the reaction medium.…”
Section: Monoacylglycerols (Mags)mentioning
confidence: 99%